George Dewey papers - Dewey, George, 1837-1917.; Dewey, Mildred McLean Hazen, 1850-1931.
Correspondence, letterbooks, diaries, journal, military papers, financial papers, scrapbooks, and other papers relating chiefly to Dewey's activities as commander of the U.S. Navy Asiatic Squadron East during the Spanish-American War, especially his command of the USS Olympia during the battle of Manila Bay. Documents his service as commander of the USS Pensacola, European Squadron (European Station), 1885-1888; president of the U.S. Navy General Board, 1899-1917; president of the court of inquiry (1901) concerning Winfield Scott Schley; and commander-in-chief of naval winter maneuvers while aboard the presidential yacht Mayflower, 1902-1903. Also includes correspondence, financial records, and other papers of Dewey's second wife, Mildred McLean Hazen Dewey, relating to family interests in the Rosiclare Lead and Fluorspar Mining Company, her estate, and other matters; letters (1874) from James A. Garfield and William T. Sherman to Mildred Dewey's first husband, William Babcock Hazen; and an account (1904) of Admiral Dewey and the Manila campaign written by Commander Nathan Sargent, U.S.N.
Family correspondents include Dewey's parents, Julius Y. Dewey and Mary Perrin Dewey, and his son, George G. Dewey. Other correspondents include Charles J. Bonaparte, Frederick M. Bugher, William E. Chandler, George B. Cortelyou, George Creel, Josephus Daniels, John W. Davis, Grenville Mellen Dodge, John Hay, Robert Lansing, Henry Cabot Lodge, John Davis Long, A.T. Mahan, John R. McLean, William H. Moody, Paul Morton, Truman Handy Newberry, Elisabeth Ellicott Poe, Redfield Procter, Theodore Roosevelt, Elihu Root, Alvin Untermyer, and Oscar Fitzalan Williams.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bonaparte, Charles J. -- 1851-1921 -- Correspondence; Bugher, Frederick M. -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Creel, George, -- 1876-1953 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Dewey, George G. -- -1963 -- Correspondence; Dewey, Julius Y. -- Correspondence; Dewey, Mary Perrin, -- -1843? -- Correspondence; Dodge, Grenville Mellen, -- 1831-1916 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Hazen, William Babcock, -- 1830-1887 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Long, John Davis, -- 1838-1915 -- Correspondence; Mahan, A. T. -- 1840-1914 -- Correspondence; McLean, John R. -- 1848-1916 -- Correspondence; Moody, William H. -- 1853-1917 -- Correspondence; Morton, Paul, -- 1857-1911 -- Correspondence; Newberry, Truman Handy, -- 1864-1945 -- Correspondence; Poe, Elisabeth Ellicott, -- 1886-1947 -- Correspondence; Proctor, Redfield, -- 1831-1908 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Sargent, Nathan, -- 1849-1907.; Schley, Winfield Scott, -- 1839-1911.; Sherman, William T. -- 1820-1891 -- Correspondence; Untermyer, Alvin, -- 1882-1963 -- Correspondence; Williams, Oscar Fitzalan, -- 1843-1909 -- Correspondence; Dewey family -- Correspondence; United States. -- Navy. -- Asiatic Squadron; United States. -- Navy. -- European Station; United States. -- Navy. -- General Board; United States. -- Navy -- History -- Spanish-American War, 1898.; United States. -- Navy -- Maneuvers; Mayflower (Yacht); Olympia (Cruiser); Pensacola (Screw steamer); Rosiclare Lead and Fluorspar Mining Company; Courts-martial and courts of inquiry -- United States; Manila Bay, Battle of, Philippines, 1898.; Spanish-American War, 1898 -- Campaigns; Naval officers